Foglalkoztatás a „Zöld” zöldséghajtató modellgazdaságokban - Agrádi, Éva; Tégla, Zsolt (Acta Carolus Robertus, 2011)
The thesis dealt with two of the area, which is nowadays a very dominant role in economic life. One of them is the use of renewable energy sources, the other one is how to increase employment. We were constructing a vegetable – forcing model farm’s heating system in accordance with the natural environment of Hungary. This system allows the efficient use of renewable energy sources. We did a cost analysis, in which we demonstrated that, which model is the most economical to operate under the given conditions and opportunities. The investments, based on renewable energy sources, have potential, that helps for the sustainable development. To this end, the aim is that the investments are sustained locally, and to reinforce the use of local human resources.